2000
DOI: 10.1029/1999jb900372
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave splitting, continental keels, and patterns of mantle flow

Abstract: Abstract. In this study we investigated the origin of seismic anisotropy in the mantle beneath North America. In particular, we evaluated whether shear wave splitting patterns in eastern North America are better explained by anisotropy caused by lithospheric deformation, anisotropy due to mantle flow beneath the lithosphere, or a combination of both. We examined new measurements of shear wave splitting from the Missouri to Massachusetts broadband seismometer array (MOMA), the North American Mantle Anisotropy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
207
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(229 citation statements)
references
References 73 publications
19
207
3
Order By: Relevance
“…Some contribution to the observed signal from the crust is likely in this splitting dataset, but anisotropy in the crust cannot explain the observed δt values up to nearly 2 s. The crustal thickness in the Ryukyu arc, ∼35-40 km (Taira, 2001), is insufficient to explain such large splitting, and observed crustal splitting times in Japan average about 0.2 s (Kaneshima, 1990). It has been demonstrated that both lithospheric and asthenospheric contributions to anisotropy are important in many regions (e.g., Fouch et al, 2000;Simons et al, 2002;Simons and van der Hilst, 2003;Fischer et al, 2005;Waite et al, 2005), although splitting measurements in subduction zone settings are nearly always interpreted in terms of flow in the asthenosphere (e.g., Fischer et al, 1998Fischer et al, , 2000Smith et al, 2001;Anderson et al, 2004). The lithosphere beneath the Ryukyu arc stations is likely to be thin, due to thermal erosion associated with mantle wedge flow (e.g., Conder et al, 2002), and it is unlikely that the lithosphere is thick enough to explain the large split times.…”
Section: Frozen Anisotropy In the Lithosphere And/or Crustmentioning
confidence: 96%
“…Some contribution to the observed signal from the crust is likely in this splitting dataset, but anisotropy in the crust cannot explain the observed δt values up to nearly 2 s. The crustal thickness in the Ryukyu arc, ∼35-40 km (Taira, 2001), is insufficient to explain such large splitting, and observed crustal splitting times in Japan average about 0.2 s (Kaneshima, 1990). It has been demonstrated that both lithospheric and asthenospheric contributions to anisotropy are important in many regions (e.g., Fouch et al, 2000;Simons et al, 2002;Simons and van der Hilst, 2003;Fischer et al, 2005;Waite et al, 2005), although splitting measurements in subduction zone settings are nearly always interpreted in terms of flow in the asthenosphere (e.g., Fischer et al, 1998Fischer et al, , 2000Smith et al, 2001;Anderson et al, 2004). The lithosphere beneath the Ryukyu arc stations is likely to be thin, due to thermal erosion associated with mantle wedge flow (e.g., Conder et al, 2002), and it is unlikely that the lithosphere is thick enough to explain the large split times.…”
Section: Frozen Anisotropy In the Lithosphere And/or Crustmentioning
confidence: 96%
“…The previous geochemical studies showed that the Eastern Block of the NCC has a thin lithosphere with thickness of $80 km [Griffin et al, 1998;Fan et al, 2000;Gao et al, 2002;Wu et al, 2003], however the range of the thinning lithosphere is still in debate. Based on our results, we proposed that the lithosphere beneath the Central Zone was thicker than that beneath the Eastern Block when the extensional event occurred, and the thicker lithosphere root of the Central Zone probably acted as a barrier deflecting the northwestward mantle flow [e.g., Fouch et al, 2000]. In this case, a compressional stress field would be introduced to cause fast polarization directions to orient NE-SW or NNE-SSW that is perpendicular to the direction of compression at the boundary.…”
Section: Discussionmentioning
confidence: 99%
“…The direct S phases obtain their initial polarization at the source. We are only interested in anisotropy beneath the seismic station, and we therefore reduce the possibility of source-side splitting by analyzing direct S events only from hypocenters deeper than 550 km, a depth beneath the possible effects of significant upper transition zone anisotropy found in some subduction zones [Fouch and Fischer, 1996]. We also do not analyze direct S phases from the Tonga-Kermadec and New Hebrides subduction zones, as evidence of strong source-side splitting has been reported for that region [Wookey et al, 2002].…”
Section: Methodology: Apparent Splitting Measurementsmentioning
confidence: 99%
“…[61] Fouch et al [2000] modeled the anisotropy expected for subcontinental mantle flow around a craton keel and found that such a model complicated by additional lithospheric anisotropy may explain shear wave splitting beneath eastern North America as well. Their calculations predict that splitting beneath this or any relatively flat lithospheric keel would have APM-parallel f, whereas splitting elsewhere would have f parallel to the depth contours at the base of the lithosphere because the rigid lithosphere is moving through the asthenosphere.…”
Section: Asthenospheric Flow With Basal Lithospheric Topography and Pmentioning
confidence: 99%